Morphology of the novel ventral scape gland in the ant genus Strumigenys. (July 2021) - Wang, Chu; Lin, Chung-Chi; Billen, Johan
Abstract: We describe a novel ventral scape gland in all 19 species of the genus Strumigenys that we examined, confirming the postulated existence of this gland by Bolton (1999). The gland occurs in workers and queens; it belongs to 'class-1' and is formed by a layer of epithelial secretory cells that line the ventrodistal tegumental cuticle of the antennal scape. The gland is characterized by its bowl-shape, by the ultrastructural characteristics of microvillar arrangement and by the presence of nerves in between the epithelial cells. These features make this gland structurally very similar to 3 other epithelial glands that occur exclusively in Strumigenys . Besides the epithelial ventral scape gland, also scattered class-3 glandular cells are found. The function of both glands in the scape remains unclear, although a role in prey attraction cannot be excluded. Graphical abstract: Image 1 Highlights: A novel ventral scape gland has been found in all 19 examined Strumigenys species. The gland occurs in both workers and queens and is probably absent in males. The epithelial gland is found near the ventrodistal tip of the scape. The gland may possibly play a role during prey hunting.